Chapter Come fermare una grande recessione. Il dibattito sulla crisi economica del 1929 in Italia - MAGLIULO, Antonio (Studi e saggi, 2021)
The aim of this essay is to assess how the debate on the Great Depression of 1929 changed Italian economic culture in the transition from Fascism to the Republic. The essay is divided into three paragraphs. In the first, we will look at the international debate dominated by the dispute between Hayek and Keynes and by Röpke's synthesis. In the second, we will analyse the debate in Italy, which is characterised by the convergent synthesis proposed by Bresciani Turroni, Einaudi and Fanno. The last section will outline the economic policy choices of the Fascist regime and the legacy of the debate on the great crisis in the period of post-war reconstruction